PRODUCTION OF MODIFIED RNA-DEPENDENT DNA POLYMERASE OF HUMAN IMMUNODEFICIENCY VIRUS FOR USE AS REVERSE TRANSCRIPTASE - Mussakhmetov, A.; Akishev, Zh.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2025)
Human immunodeficiency virus reverse transcriptase is an RNA-dependent DNA polymerase that allows the production of complementary DNA on an RNA matrix. The original amino acid sequence of the reverse transcriptase was modified by making 18 substitutions and codonoptimized for expression in Escherichia coli cells. A plasmid vector in which the modified HIV reverse transcriptase gene was integrated under the control of the inducible promoter was obtained by restriction-free cloning. Transformation of competent E. coli cells with this vector yielded a strain producing recombinant modified HIV reverse transcriptase with a molecular mass of 62.5 kDa. The recombinant enzyme was chromatographically purified by two-step elution on Ni2+ ions and heparin, yielding 420 mg from 1 liter of induced culture. The RNA-dependent DNA polymerase activity of the purified enzyme was confirmed on RNA samples isolated from Secale cereale and human blood by amplification of 18S rRNA and actin B gene fragments, respectively. The recombinant modified reverse transcriptase exhibits polymerase activity in the temperature range of 50-70ºС, indicating its thermostability. Biochemical parameters show the promising application of the enzyme as a reverse transcriptase in scientific research and diagnostic practice.